Diffuse and Focal Corticospinal Tract Disease and Its Impact on Patient Disability in Multiple Sclerosis. Issue 2 (16th October 2014) - Tovar‐Moll, Fernanda; Evangelou, Iordanis E.; Chiu, Annie W.; Auh, Sungyoung; Chen, Christina; Ehrmantraut, Mary; Ohayon, Joan M.; Richert, Nancy; Bagnato, Francesca
ABSTRACT: BACKGROUND AND PURPOSE: We investigated the impact of focal and diffuse corticospinal tracts damage on sensory‐motor disability in multiple sclerosis (MS) patients. METHODS: Twenty‐five MS patients underwent 3.0 Tesla (3T) magnetic resonance imaging with diffusion tensor imaging (DTI). The Expanded Disability Status Scale (EDSS) and the Timed 25‐Foot Walk test (T25FW) quantified patient physical disability. Fractional anisotropy (FA) and mean diffusivity (MD) of the corticospinal tracts, whole brain and corticospinal tracts lesion volume were also computed. Spearman rank correlation analyses measured the associations between DTI‐derived metrics and other measures of disease. Partial correlation analyses between DTI and disability measures were performed and corrected for lesion volumes as appropriate. RESULTS: Significant associations were seen between FA of the corticospinal tracts and EDSS ( r = −.500, P = .0011), motor‐EDSS ( r = −.519, P = .008), and T25WF ( r = −.637, P = .001) scores and MD of the corticospinal tracts and motor‐EDSS ( r = .469, P = .018) and T25WF ( r = .428, P = .033) scores. When correcting for lesion volumes, only the association between FA of the corticospinal tracts and EDSS ( r ≤ −.516, p ≤ .01) or motor‐EDSS score ( r ≤ −.516, p ≤ .01) persisted. CONCLUSIONS: DTI at 3T shows that the impact of diffuse corticospinal tracts disease on sensory‐motor disability is greatly mediated by focal lesions in MS.